Informed consent practices in oral and maxillofacial surgery setups – an audit report - Irfan Shah; Rafia Aneeqa Lahooti; Muhammad Nazir Khan (Journal of the Pakistan Medical Association, 2021)
Abstract Objective: The objective of this study was to evaluate the existing practices of obtaining and documenting informed consent in the specialty of oral and maxillofacial surgery. Continuous...